The Struggle of Finding Identity as Seen in Mark Twain’s The Adventures of Tom Sawyer - Raflis Raflis; Ester Rani Julchardilla Harita (Jurnal Ilmiah Pendidikan Scholastic, 2023)
The title of this research is "The Struggle to Find Identity as Seen in Mark Twain's Novel The Adventurs of Toms Sawyer". The problem of this research is focused on Tom's struggles using Kennedy's (2016) theory, Tom's adventures which reflect his true identity using Mark and June's (2012) theory and external conflicts experienced by Tom as reflected in Mark Twain's novel The Adventures of Tom Sawyer using Kenny's (1966) theory. The approach used in this research is psychology. This research is a qualitative descriptive research. The technique used in this study is a documentary based on Mason. The results of this study indicate that all of Tom's struggles in this novel are based on the majority of people who always think that Tom is a delinquent, naughty boy. And Tom's struggle to get the girl he loves so much. It took a struggle to prove that Tom was actually a good boy. The adventures of Tom, who is looking for his true identity, is caused by the people of evaluate, that Tom is a very naughty child and the attitude of the whole society, which is often unpleasant, finally makes him look for happiness or pleasure with adventure, which in the end, his adventures make his identity change from the beginning. always known as a naughty child who turns into a good, smart child and becomes a role model in the village. The external conflict occurs because sometimes humans disagree with other people because of their mischief.